Predictors of psychosocial well-being in patients seeking fertility treatment in South Africa - Kitso Setswe; Rizwana Roomaney (Middle East Fertility Society Journal)
Abstract Background Psychosocial well-being encompasses emotional, psychological, and social health. Infertility can negatively impact psychosocial well-being, particularly in pronatalist societies. This study investigates the predictors of psychosocial well-being among fertility patients in South Africa. Results Participants reported moderate to high psychosocial well-being (M = 193.90, SD = 27.80) but elevated levels of anxiety, depression (M = 14.41, SD = 7.37), and fertility-related stress (M = 31.59, SD = 10.65). Regression analysis revealed that psychosocial factors, particularly anxiety, depression (β = − 0.44, p < 0.001), relationship quality (β = 0.27, p < 0.001), and fertility-related stress (β = − 0.16, p = 0.023), accounted for 46.5% of the variance in well-being (R 2 = 0.465). Demographic (gender, marital status, education level, and income) and clinical factors (recruitment site and time taken before seeing a doctor) did not significantly predict well-being. Conclusion Psychosocial factors, particularly anxiety, depression, relationship quality, and fertility-related stress, were significant predictors of well-being in fertility patients.